2006
DOI: 10.1523/jneurosci.4398-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Unpredictable Stress Exacerbates Lipopolysaccharide-Induced Activation of Nuclear Factor-κB in the Frontal Cortex and Hippocampus via Glucocorticoid Secretion

Abstract: Although the anti-inflammatory actions of glucocorticoids (GCs) are well established in the periphery, these stress hormones can increase inflammation under some circumstances in the brain. The transcription factor nuclear factor-B (NF-B), which is inhibited by GCs, regulates numerous genes central to inflammation. In this study, the effects of stress, GCs, and NMDA receptors on lipopolysaccharide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
244
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 252 publications
(275 citation statements)
references
References 52 publications
21
244
0
10
Order By: Relevance
“…The studies that have looked at the effects of chronic GC exposure have also found similar results for basal GCs: locking GCs at basal levels augments excitotoxin-induced upregulation of IL-1β and TNF-α expression and protein levels in the hippocampus (Dinkel et al 2003). Pharmacological inhibition of GR increases TNF-α, IL-1 beta, and iNOS protein levels in rats given LPS peripherally (Munhoz et al 2006). Moreover, in hippocampal cultures, low concentrations of corticosterone inhibit excitotoxin-induced expression of IL-1β and TNF-α (MacPherson et al 2005).…”
Section: 3mentioning
confidence: 70%
See 4 more Smart Citations
“…The studies that have looked at the effects of chronic GC exposure have also found similar results for basal GCs: locking GCs at basal levels augments excitotoxin-induced upregulation of IL-1β and TNF-α expression and protein levels in the hippocampus (Dinkel et al 2003). Pharmacological inhibition of GR increases TNF-α, IL-1 beta, and iNOS protein levels in rats given LPS peripherally (Munhoz et al 2006). Moreover, in hippocampal cultures, low concentrations of corticosterone inhibit excitotoxin-induced expression of IL-1β and TNF-α (MacPherson et al 2005).…”
Section: 3mentioning
confidence: 70%
“…Commensurate with that, in unstressed rats, GR antagonists increase LPS-induced NFκB DNA binding activity in the frontal cortex and hippocampus (Munhoz et al 2006). Moreover, dexamethasone treatment decreases basal NFκB DNA binding activity in cortex and hippocampus (Unlap and Jope 1995;Unlap and Jope 1997) and also following LPS treatment (Wang et al 2006) (however there are some caveats to this interpretation that will be discussed later.…”
Section: 3mentioning
confidence: 71%
See 3 more Smart Citations